Realitas Adati Hula-Hulaa to Syara’i, Syara’i Hula-Hulaa to Qur’ani - Mashadi Mashadi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2012)
Islam has become the support and reference among Gorontalo people from the early period the religion. It is including in their way of life and daily activity such as daily lives and traditions. Therefore, it can be understood that Gorontalo is known with the philosophical